The Dampak Pola Komunikasi Keluarga Terhadap Stabilitas Emosional dan Pembentukan Konsep Diri Anak: PROBLEMATIKA PEMBELAJARAN ILMU NAHWU: TINJAUAN LITERATUR ATAS PENGGUNAAN METODE BANDONGAN (ARAB PEGON) - Grafda Kaiki; Muhammad Afthon Ulin Nuha (LUGHATI: Jurnal Pendidikan Bahasa Arab, 2026)
Nahwu learning in pesantren (Islamic boarding school) environments often employs the bandongan method, a one-way teaching model where the instructor reads, translates, and explains the classical book, while the students note the meaning using Pegon Arabic script. Although this method has become a deeply rooted tradition, its effectiveness in achieving a comprehensive understanding of Nahwu remains debated. This study aims to analyze the challenges and effectiveness of using makna gandul (Pegon Arabic script notes) in Nahwu learning through a literature review. The method used is a library study, examining relevant theories, pedagogical methods, and previous research findings. The review results indicate that the bandongan method has several weaknesses, such as a passive learning process, limited mastery of the Pegon script, local language barriers, and difficulty in understanding the text holistically. However, this method still has advantages, especially in helping students directly identify sentence structures. With the passage of time, adaptations such as the addition of discussion sessions are beginning to increase the communicative nature of this method. Thus, the effectiveness of the bandongan method is highly dependent on context, student readiness, and the accompanying pedagogical innovations.